2017
DOI: 10.1007/s11356-017-0898-x
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition in rainbow trout tissues from a fish farm from Patagonia, Argentina

Abstract: Rainbow trout is a salmonid specie of commercial importance raised in hatcheries in many countries. Studies over mineral requirements have being perform to guarantee the fulfillment of the nutritional needs and therefore improving the fish farm productions. The aim of this work was to investigate the performance of the elements like Ag, As, Br, Ca, Cr, Cs, Fe, Hg, K, Na, Rb, Se, and Zn, in rainbow trout from a Patagonian fish farming. Body burden of each element in relation to weight were analyzed for identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…In the case of burbot, smaller-sized juveniles with higher arsenic in the nearfield area (top panel, Fig 3) were captured in the vicinity of the effluent outflow for Giant Mine and were likely exposed to higher arsenic levels compared with larger individuals that resided in less impacted areas of the nearfield. Although size and age effects on arsenic concentrations in fishes have been reported in the literature [19, 71], the results from this study are consistent with findings that arsenic is eliminated relatively quickly from fish [8, 61, 72]. Arsenic bioaccumulated more in the higher exposure nearfield area, but no evidence was found for long-term increases with age for long-lived, slow growing subarctic fishes in this study.…”
Section: Discussionsupporting
confidence: 89%
“…In the case of burbot, smaller-sized juveniles with higher arsenic in the nearfield area (top panel, Fig 3) were captured in the vicinity of the effluent outflow for Giant Mine and were likely exposed to higher arsenic levels compared with larger individuals that resided in less impacted areas of the nearfield. Although size and age effects on arsenic concentrations in fishes have been reported in the literature [19, 71], the results from this study are consistent with findings that arsenic is eliminated relatively quickly from fish [8, 61, 72]. Arsenic bioaccumulated more in the higher exposure nearfield area, but no evidence was found for long-term increases with age for long-lived, slow growing subarctic fishes in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have also shown differences in arsenic body burdens related to feeding habits. For example, arsenic concentrations in muscle of rainbow trout from a Patagonian fish farming feeding commercial food, were found higher (1.5 -3.2 µg g −1 DW) than similar sized wild rainbow trout analyzed in this study, and that was consistent with the higher arsenic concentration present in the commercial food provided (Bubach et al, 2018). Moreover, in other freshwater systems higher body levels of total arsenic were found in bottom feeding fish compared to forage fish, while predatory fish presented the lowest body levels overall (Chen and Folt, 2000;Kirby and Maher, 2002;Suhendrayatna and Maeda, 2001).…”
Section: Speciessupporting
confidence: 87%
“…Therefore, in lodge to prepare economic diets, alternative plant protein sources such as grains, pulses and oilseeds are widely used [1]. Positive impacts of good compounds in fish are badly impressed by the presence of toxic compounds in water body and fish body and also have an adverse consequence on human health when humans consume such fishes according to [2].…”
Section: Introductionmentioning
confidence: 99%